An advanced hospital rating system using machine learning and natural language processing - Tamjid, Ali Asgar; Galpo, Gaurab Paul; Urmi, Khadija Begum; Chitto, Fatema Sadeque; Annafi, Sadia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.